Intrinsic network reactivity differentiates levels of consciousness in comatose patients. Issue 11 (November 2018) - Khanmohammadi, Sina; Laurido-Soto, Osvaldo; Eisenman, Lawrence N.; Kummer, Terrance T.; Ching, ShiNung
Highlights: Intrinsic brain dynamics distinguish different levels of consciousness in comatose patients. Reaching low variance EEG activation patterns becomes harder for lower levels of consciousness. The Intrinsic Network Reactivity Index is robust to etiological and pharmacological heterogeneity. Abstract: Objective: We devise a data-driven framework to assess the level of consciousness in etiologically heterogeneous comatose patients using intrinsic dynamical changes of resting-state Electroencephalogram (EEG) signals. Methods: EEG signals were collected from 54 comatose patients (GCS  ⩽  8) and 20 control patients (GCS  >  8). We analyzed the EEG signals using a new technique, termed Intrinsic Network Reactivity Index (INRI), that aims to assess the overall lability of brain dynamics without the use of extrinsic stimulation. The proposed technique uses three sigma EEG events as a trigger for ensuing changes to the directional derivative of signals across the EEG montage. Results: The INRI had a positive relationship with GCS and was significantly different between various levels of consciousness. In comparison, classical band-limited power analysis did not show any specific patterns correlated to GCS. Conclusions: These findings suggest that reaching low variance EEG activation patterns becomes progressively harder as the level of consciousness of patients deteriorate, and provide a quantitative index based on passive measurements that characterize this change. Significance: Our results emphasize the role of intrinsic brain dynamics in assessing the level of consciousness in coma patients and the possibility of employing simple electrophysiological measures to recognize the severity of disorders of consciousness (DOC).